PROBLEMS OF EDUCATION IN INDONESIA AND ALTERNATIVE SOLUTIONS - Madhakomala, R.; Hakim, M. Akrimul; Syifauzzuhrah, Nabillah (International Journal of Business, Law, and Education, 2022)
Today, education in Indonesia is assessed by various groups, both at home and abroad, has been facing various challenges and problems so that it has a negative impact on low quality of education in Indonesia. For this reason, this research was deliberately carried out as a contributive step to identify various challenges and problems faced by the world of education in Indonesia and recommend several solution steps so that they can contribute ideas to improve education in Indonesia. This research uses the qualitative approach by applying the literature study method as well as collecting primary data and various secondary sources through documentation, followed by analysis of the data obtained. From the research conducted, it can be found that there are several challenges and problems of education in Indonesia, including unbalanced education output, low quality of facilities and infrastructure, low quality and behavior of teachers, student moral behavior, and tolerance for racial intolerance. In order to overcome the problems above, it is necessary to have mutual cooperation and collaboration from all parts of nation as the key to implementing several alternative solutions, including improving the welfare of education, building a world view and improving the mindset of teachers and students, developing a comprehensive curriculum design, overseeing budget allocations, increase the contribution of the business world and others.